2015
DOI: 10.4314/ajcem.v16i3.6
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> activity of fosfomycin against uropathogen multi-drug resistant (MDR)<i> Pseudomonas aeruginosa</i> and <i>Acinetobacter baumannii</i>

Abstract: Urinary tract infections caused by multidrug resistant Gram negative bacilli constitute a major global healthcare problem. Fosfomycin is considered the best treatment option for such infections. Urine samples were collected and cultured in a tertiary care hospital (Urology). Identification of these uropathogens and their antibiotic sensitivity screening were performed according to CLSI guidelines. Urine samples (n=436) were selected in which Ps. aeruginosa and Acinetobacter baumannii were found to be the signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…,( >60) , & we concluded that UTI incidence was higher in the age group of 16-40 (43.72%) and 41-60 (24.91%). A similar study was conducted by Laari et al,(38) (2022) in Ghana (West Africa) to understand the aspect of age as a determinant of UTIs. The(…”
mentioning
confidence: 75%
“…,( >60) , & we concluded that UTI incidence was higher in the age group of 16-40 (43.72%) and 41-60 (24.91%). A similar study was conducted by Laari et al,(38) (2022) in Ghana (West Africa) to understand the aspect of age as a determinant of UTIs. The(…”
mentioning
confidence: 75%
“…The management and treatment of bacterial RTIs have historically relied on the use of antibiotics. However, the efficacy of these drugs is increasingly compromised by the emergence and spread of multi-drug resistant (MDR) bacteria [4]. The World Health Organization has identified antibiotic resistance as one of the biggest threats to global health, food security, and development today.…”
Section: Introductionmentioning
confidence: 99%